2004
DOI: 10.1097/01.ccm.0000134354.20449.b2
|View full text |Cite
|
Sign up to set email alerts
|

Secondary confirmation of endotracheal tube position by ultrasound image

Abstract: Ultrasound imaging of diaphragm motion is a useful, quick, noninvasive, portable, and direct anatomic method for assessment of ET tube position. We think it should be considered the method of choice for the secondary confirmation of the ET tube position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 13 publications
0
96
0
Order By: Relevance
“…It is not the first time that a precision study is carried out with this purpose. Available data, however, result inconclusive, since technical issues were raised [12] and conflicting data currently exist [10]. We found the fifth percentile of diaphragm motion to be 17.7 and 13.5 mm at QB, and 62.6 and 49.6 mm at DB for the male and female population, respectively.…”
Section: Discussionmentioning
confidence: 64%
“…It is not the first time that a precision study is carried out with this purpose. Available data, however, result inconclusive, since technical issues were raised [12] and conflicting data currently exist [10]. We found the fifth percentile of diaphragm motion to be 17.7 and 13.5 mm at QB, and 62.6 and 49.6 mm at DB for the male and female population, respectively.…”
Section: Discussionmentioning
confidence: 64%
“…The diaphragm and lung movements, which are qualitative and quantitative signs that the lungs are properly ventilated, can be directly and easily documented by US [16]. If the movements of the diaphragm are symmetrical on both sides, and intercostal US scan shows the presence of bilateral lung sliding synchronous with the ventilation, it can be inferred that the endotracheal tube is correctly placed in the trachea [17,18]. In cases of esophageal intubation, assisted ventilation is not followed by lung expansion, but the diaphragm movements may follow the patient's spontaneous breathing if it has not been pharmacologically suppressed.…”
Section: Us Assessment Of the Airwaymentioning
confidence: 99%
“…Besides visualization of the endotracheal tube within the trachea, other studies have confirmed with ultrasound (US) that successful intubation with an ETT had occurred using either the sliding lung sign of visceral-parietal pleural movement [2,3,4] or by diaphragmatic motion along the lateral chest wall [5,6]. …”
Section: Introductionmentioning
confidence: 99%